UTeM`s Amphibious Hybrid Vehicle: Ride and Handling Analysis - Hassan, Muhammad Zahir; Abdul Manaf, Muhammad Zaidan; Halid, Mohd Shazni; Alehan, Muhammad Nadzeer; Md Isa, Amjad Saddar (Trans Tech Publications, Switzerland, 2013)
The vehicle ride and handling analysis is one of the important aspects in vehicle dynamics. This paper takes a model of amphibious vehicle to establish the exact virtual behavior of vehicle’s riding and handling base on the virtual design parameter. This vehicle can operate both on ground and water, therefore the analysis model is developed using seven degree of freedom model for ground operation and one degree of freedom model for water operation. The seven DOF are moment of roll, pitch, yaw and all four tires motion while the rest is buoyancy. Therefore, the ability and limitation of the vehicle demonstrate the behavior of unexpected case happened. These facts in turn to be used to improve the ride and handling level during acceleration, deceleration, cornering and step steer. The model also capable to function on the water where as the design of the body work considers the buoyancy concept for stability on every condition of wave surface. The analysis of buoyancy and stability for this model shows the vehicle ability to perform in the state of equilibrium condition under heeling and capsizing on water surface.